A concept as a diachronic phenomenon: heuristic comparative historical analysis (based on the "purity" lexical-semantic field in the German and English languages) - Dronova, Lyubov P. (Procedia - Social and Behavioral Sciences)
The article is devoted to improving the methods of conceptual analysis to represent the concept in its evolution. To solve this problem it is proposed to bring the tools of modern comparative science relying on an integrative method. The effectiveness of cooperation between two areas of linguistics at the level of diachronic analysis techniques in the article is demonstrated, firstly, in terms of the possibility of mutual verification of results. Secondly, the effectiveness of such interaction is shown by the example of the use of diachronic research as the initial stage of conceptual analysis in the reconstruction of the concept evolution.